2019
DOI: 10.3390/su11174738
|View full text |Cite
|
Sign up to set email alerts
|

Science Mapping of Tourist Mobility 1980–2019. Technological Advancements in the Collection of the Data for Tourist Traceability

Abstract: The tracking of tourist movements is an essential aspect in the management of sustainable tourist destinations. The current information and communication technologies provide innovative ways of collecting data on tourist movements, but it is still necessary to evaluate tools and methods of study for this challenge. At this point, mobile technologies are the best candidate for this task. Given the relevance of the topic, this paper proposes a mapping science analysis of publications on "movement of tourists" an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 253 publications
(162 reference statements)
0
16
0
Order By: Relevance
“…Previous research on intra-destination behaviour has mainly been based on analysing spatio-temporal flows or mobility patterns, while, until now, participation patterns have been studied in a secondary stage (Chantre-Astaiza et al, 2019;Grinberger & Shoval, 2019;Xu et al, 2019). The main theoretical contribution of this paper is therefore the proposal of a consistent three-dimensional framework that integrates spatial movement, temporal consumption and interaction with attractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on intra-destination behaviour has mainly been based on analysing spatio-temporal flows or mobility patterns, while, until now, participation patterns have been studied in a secondary stage (Chantre-Astaiza et al, 2019;Grinberger & Shoval, 2019;Xu et al, 2019). The main theoretical contribution of this paper is therefore the proposal of a consistent three-dimensional framework that integrates spatial movement, temporal consumption and interaction with attractions.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest studies in the context of intra-destination behaviour focus on the spatiotemporal dimensions in order to discover intra-destination mobility patterns (Hall, 2005;Lew & McKercher, 2006;McKercher & Lew, 2004). However, recent studies have highlighted that the traditional spatio-temporal framework does not consider the effect of facts and experiences when examining tourist mobility (Chantre-Astaiza et al, 2019;Han et al, 2018;Xu et al, 2019). Even more recently, Grinberger and Shoval (2019, p.512) introduced a new term to refer to this complex phenomenon, 'tourist activity patterns', "resulting from the interaction between time-space constraints and the cognitive, social, cultural and emotional tourists' factors".…”
Section: Introductionmentioning
confidence: 99%
“…After this confirmation, the possibility of creating tourist itineraries was considered by taking as a reference the most visited municipalities and the Historical Ensembles that would be viable, as it has been shown that tourist mobility patterns can be extracted [73][74][75][76]. From all of this, it can be gathered that the most visited municipalities (origin) and the Historical Ensembles (destination) were taken as a reference to establish the itineraries.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, big data, geographic information systems (GIS), computer simulation and other technologies have been applied widely in the field of tourism spatial planning research. Moreover, smartphones and travel websites provide strong technical support for smart tourism, due to the progress of social media [5], [6]. There are many forms of big data collection and application, among which visual analysis is frequently used.…”
Section: Research Backgroundmentioning
confidence: 99%